Characterization Of Magnetic Susceptibility Values Of Pumice From Matur Areas Using The Rock-Magnetic Method - Junia, Retna; Hamdi, Hamdi (Jurnal Pendidikan Tambusai, 2025)
The value of magnetic susceptibility can determine the magnetic properties and the type of magnetic minerals contained in the material. This mineral is often found in rocks, one of which is pumice. The distribution of pumice is very widespread in various places such as in the Matur area, Agam Regency, West Sumatra, where many volcanic materials are found in the form of pumice from volcanic eruptions. However, no one has studied the magnetic susceptibility of pumice in the Matur area. This study aims to characterize the magnetic susceptibility contained in pumice in the Matur area using rock magnetism methods. This method is very effective, fast, inexpensive, and non-destructive. Magnetic susceptibility measurements using Bartington Magnetic Susceptibility Meter (MS2B) with two frequencies, namely 0.47 kHz low frequency and 4.7 kHz high frequency. The magnetic susceptibility value of pumice in the Matur area has the smallest  value of  28.7 x  and the largest  value is 205.1 x  kg with an average   value of 165.7 x . As for the smallest  (%) value is 0.1% and the largest  (%) value is 1.5% with an average  (%) value of 0.9%. With the measured MS2B measurements, the results show that pumice in the Matur area belongs to the antiferromagnetic mineral group and has almost no superparamagnetic grains.